The design, synthesis and characterisation of subtype selective dipeptide-linked fluorescent ligands for human β1 and β2–adrenoceptors - Santu, L.T. (2017)
Beta-adrenoceptors belong to the superfamily of G-protein coupled receptors (GPCR) and remain an important target for drug discovery. The complexity of GPCR pharmacology in terms of its signaling profile has led to a desire to further the study of receptor-ligand interaction and obtain more detailed information regarding ligand affinity and efficacy. Development of selective fluorescent ligands targeted at human β1 and β2–adrenoceptors may facilitate drug discovery programs in terms of understanding receptor pharmacology and receptor localisation in both recombinant and primary cells from healthy and diseased tissue. Fluorescent ligands are usually designed and synthesized by tethering the ligand to a fluorophore via a linker to form a conjugate. This thesis reports the synthesis of a series of novel dipeptide-linked congeners which, when coupled to commercially available fluorophore active esters (BODIPY-X-630/650 or BODIPY–FL), afford a series of seventeen red- and green-emitting dipeptide-linked fluorescent ligands for human β1 and β2–adrenoceptors.